Decorative planting and flower composition features in cemeteries decoration - О.А. Kushnir (Інтродукція Рослин, 2005)
There are classifications of decorative plants of burial places: the basic conditions which influence on horticulture style choice and assortment of plants, most frequently used on cemeteries in the article.